Causes of community-acquired bacteremia and patterns of antimicrobial resistance in Vientiane, Laos - Rattanaphone Phetsouvanh (2018)
There is no published information on the causes of bacteremia in the Lao PDR (Laos). Between 2000 and 2004, 4512 blood culture pairs were taken from patients admitted to Mahosot Hospital, Vientiane, Laos, with suspected community-acquired bacteremia; 483 (10.7%) cultures grew a clinically significant community-acquired organism, most commonly Salmonella enterica serovar typhi (50.9%), Staphylococcus aureus (19.0%), and Escherichia coli (12.4%). S. aureus bacteremia was common among infants (69.2%), while children 1-5 years had a high frequency of typhoid (44%). Multi-drug-resistant S. Typhi was rare (6%). On multiple logistic regression analysis, typhoid was associated with younger age, longer illness, diarrhea, higher admission temperature, and lower peripheral white blood cell count than non-typhoidal bacteremia. Empirical parenteral ampicillin and gentamicin would have some activity against ∼ 88% of clinically significant isolates at a cost of US $1.4/day, an important exception being B. pseudomallei. Bacteremic infants in this setting require an anti-staphylococcal antibiotic. Copyright © 2006 by The American Society of Tropical Medicine and Hygiene.